Proximity-induced covalent labeling of proteins with a reactive fluorophore-binding peptide tag - Sünbül, Murat; Nacheva, Lora; Jäschke, Andres (Bioconjugate chemistry, 2015)
Labeling of proteins with fluorescent dyes in live cells enables the investigation of their roles in biological systems by fluorescence microscopy. Because the labeling procedure should not disturb the native function of the protein of interest, it is of high importance to find the optimum labeling method for the problem to be studied. Here, we developed a rapid one-step method to covalently and site-specifically label proteins with a TexasRed fluorophore in vitro and in live bacteria. To this end, a genetically encodable TexasRed fluorophore-binding peptide (TR512) was converted into a reactive tag (ReacTR) by adjoining a cysteine residue which rapidly reacts with N-α-chloroacetamide-conjugated TexasRed fluorophore owing to the proximity effect; ReacTR tag first binds to the TexasRed fluorophore and this interaction brings the nucleophilic cysteine and the electrophilic N-α-chloroacetamide groups in close proximity. Our method has several advantages over existing methods: (i) it utilizes a peptide tag much smaller than fluorescent proteins, the SNAP, CLIP, or HaLo tags; (ii) it allows for labeling of proteins with a small, photostable, red-emitting TexasRed fluorophore; (iii) the probe used is very easy to synthesize; (iv) no enzyme is required to transfer the fluorophore to the peptide tag; and (v) labeling yields a stable covalent product in a very fast reaction.